In vitro fibroblasts viability and migration stimulation of Acalypha indica: an insight on wound healing activity - Ammar Mahmoud Ibrahim; Mariani Abdul Hamid; Rama Ali Althiab; Amir Husni Mohd Shariff; Razauden Mohamed Zulkifli (SpringerOpen, 2021)
Abstract Background The current study investigates the antioxidant activity of Acalypha indica aerial parts and root ethanolic extracts and explore whether these extracts will stimulate fibroblasts viability and ability to migrate. Results Aerial parts extract exhibited higher DPPH scavenging activity compared to root extract with IC50 of 62 µg/mL and 206 µg/mL, respectively. Both aerial parts and root extracts showed low cytotoxicity towards fibroblasts with 753 µg/mL LD50 for aerial parts and undetected LD50 for root extract. Additionally, aerial parts extract significantly induces fibroblasts proliferation up to 134%. Wound closure investigation showed a significant closure percentage for aerial parts compared to untreated control with 75% at 1 µg/mL and high closure percentage with 70% at 0.1 µg/mL for root extract compared to only 59% closure percentage for untreated control after 48 h of the study. Conclusions This study provided evidence for A. indica to have great wound healing potential. The finding builds the scientific background in future to utilise the high antioxidant activity of A. indica and its ability to stimulate fibroblasts migration and proliferation for further applications.